Functional conservation and divergence of SEPALLATA-like genes in floral development in Cymbidium sinense - Lin, Zeng-Yu; Zhu, Gen-Fa; Lu, Chu-Qiao; Gao, Jie; Li, Jie; Xie, Qi; Wei, Yong-Lu; Jin, Jian-Peng; Wang, Feng-Lan; Yang, Feng-Xi (Frontiers in Plant Science, 2023)
Cymbidium sinense is one of the most important traditional Chinese Orchids due to its unique and highly ornamental floral organs. Although the ABCDE model for flower development is well-established in model plant species, the precise roles of these genes in C. sinense are not yet fully understood. In this study, four SEPALLATA-like genes were isolated and identified from C. sinense. CsSEP1 and CsSEP3 were grouped into the AGL9 clade, while CsSEP2 and CsSEP4 were included in the AGL2/3/4 clade. The expression pattern of CsSEP genes showed that they were significantly accumulated in reproductive tissues and expressed during flower bud development but only mildly detected or even undetected in vegetative organs. Subcellular localization revealed that CsSEP1 and CsSEP4 were localized to the nucleus, while CsSEP2 and CsSEP3 were located at the nuclear membrane. Promoter sequence analysis predicted that CsSEP genes contained a number of hormone response elements (HREs) and MADS-box binding sites. The early flowering phenotype observed in transgenic Arabidopsis plants expressing four CsSEP genes, along with the expression profiles of endogenous genes, such as SOC1, LFY, AG, FT, SEP3 and TCPs, in both transgenic Arabidopsis and C. sinense protoplasts, suggested that the CsSEP genes played a regulatory role in the flowering transition by influencing downstream genes related to flowering. However, only transgenic plants overexpressing CsSEP3 and CsSEP4 caused abnormal phenotypes of floral organs, while CsSEP1 and CsSEP2 had no effect on floral organs. Protein-protein interaction assays indicated that CsSEPs formed a protein complex with B-class CsAP3-2 and CsSOC1 proteins, affecting downstream genes to regulate floral organs and flowering time. Our findings highlighted both the functional conservation and divergence of SEPALLATA-like genes in C. sinense floral development. These results provided a valuable foundation for future studies of the molecular network underlying floral development in C. sinense.